Dietary supplementation practices in Canadian high-performance athletes - Lun, V.; Erdman, K. A.; Fung, T. S.; Reimer, R. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2012)
Dietary supplementation is a common practice in athletes with a desire to enhance performance, training, exercise recovery, and health. Supplementation habits of elite athletes in western Canada have been documented, but research is lacking on supplement use by athletes across Canada. The purpose of this descriptive study was to evaluate the dietary supplementation practices and perspectives of high-performance Canadian athletes affiliated with each of the country`s eight Canadian Sport Centres. Dietitians administered a validated survey to 440 athletes (63% women, 37% men; M =19.99 ± 5.20 yr) representing 34 sports who predominantly trained =16 hr/wk, most competing in "power" based sports. Within the previous 6 months, 87% declared having taken =3 dietary supplements, with sports drinks, multivitamin and mineral preparations, carbohydrate sports bars, protein powder, and meal-replacement products the most prevalent supplements reported. Primary sources of information on supplementation, supplementation justification, and preferred means of supplementation education were identified. Fifty-nine percent reported awareness of current World Anti-Doping Agency legislation, and 83% subjectively believed they were in compliance with such antidoping regulations. It was concluded that supplementation rates are not declining in Canada, current advisors on supplementation for this athletic population are not credible, and sports medicine physicians and dietitians need to consider proactive strategies to improve their influence on supplementation practices in these elite athletes.